2021
DOI: 10.1038/s41598-021-03389-3
|View full text |Cite
|
Sign up to set email alerts
|

A new type of non-Hermitian phase transition in open systems far from thermal equilibrium

Abstract: We demonstrate a new type of non-Hermitian phase transition in open systems far from thermal equilibrium, which can have place in the absence of an exceptional point. This transition takes place in coupled systems interacting with reservoirs at different temperatures. We show that the spectrum of energy flow through the system caused by the temperature gradient is determined by the $$\varphi^{4}$$ φ 4 -potential. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Appendix C: Explicit expressions for Eqs. ( 23)- (24) In this Appendix, we obtain explicit expressions for coefficients A, B, C, F, T, Q, Y in Eqs. ( 23)-( 24) and coefficients 20)- (21).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Appendix C: Explicit expressions for Eqs. ( 23)- (24) In this Appendix, we obtain explicit expressions for coefficients A, B, C, F, T, Q, Y in Eqs. ( 23)-( 24) and coefficients 20)- (21).…”
Section: Discussionmentioning
confidence: 99%
“…Interest to strong coupling regime is also related to control of energy transport in open quantum systems [23,24]. In [24], it has been demonstrated that in strong coupling regime a new type of phase transition appears.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations